2014
DOI: 10.1017/s0950268814001733
|View full text |Cite
|
Sign up to set email alerts
|

Under-reporting of notifiable infectious disease hospitalizations: significant improvements in the Irish context

Abstract: Notification of infectious disease is essential for prompt public health action and epidemiological analysis. The aim of this study was to compare national hospitalization data to national notification data in order to assess if there was significant under-reporting of hospitalized notifiable infectious diseases in recent years in Ireland. All in-patient discharges from public hospitals in the Republic of Ireland from 2006 to 2011 with a principal diagnosis of a notifiable disease were compared with national n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
4
1
Order By: Relevance
“…Despite the difficulty of cross-country comparisons, and the methodological difference between this study and the American study, our study finding suggests low compliance, particularly in light of South Africa’s high TB disease burden and the fact that TB is the most common notifiable disease [ 43 ]. The reported compliance in our study is also lower than a 2014 Irish study which found 98% compliance, when hospital data was compared to notifications [ 33 ], and a Taiwan study which found 83.5% compliance amongst HCPs [ 23 ]. In Africa, a Nigerian state study found that only 38.2% of HCPs were aware of notifications and 71% reported disease notification [ 29 ].…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…Despite the difficulty of cross-country comparisons, and the methodological difference between this study and the American study, our study finding suggests low compliance, particularly in light of South Africa’s high TB disease burden and the fact that TB is the most common notifiable disease [ 43 ]. The reported compliance in our study is also lower than a 2014 Irish study which found 98% compliance, when hospital data was compared to notifications [ 33 ], and a Taiwan study which found 83.5% compliance amongst HCPs [ 23 ]. In Africa, a Nigerian state study found that only 38.2% of HCPs were aware of notifications and 71% reported disease notification [ 29 ].…”
Section: Discussioncontrasting
confidence: 89%
“…Despite this legal obligation, underreporting of notifiable diseases is a common problem for passive surveillance systems in all countries, regardless of income [ 8 – 32 ]. Many high-income countries (HICs) [ 8 , 15 , 18 , 33 ] have introduced measures to make it compulsory for laboratories to notify communicable diseases and have dual reporting systems in order to overcome the problem of under-reporting. However, the strong laboratory networks in these HICs proved effective in improving the functioning of the NDSS.…”
Section: Introductionmentioning
confidence: 99%
“…These hospital datasets are the most complete data available in England to report historic population-based incidence of cases termed as viral meningitis. Other sources of data are statutory infectious disease notifications, which are frequently incomplete; 24 mortality statistics from death registrations, which do not provide disease burden estimates; and microbiologically confirmed cases reported to Public Health England, which have incomplete ascertainment. Microbiologically confirmed datasets are limited, because they do not include cases of with no pathogen identified, which are the majority in these data.…”
Section: Discussionmentioning
confidence: 99%
“…It is also crucial to identify and understand the unique characteristics of certain diseases; some diseases have a higher number of reported cases, but only a few patients have serious illnesses (eg, measles). Another electronic reporting system was used in Ireland to reduce the underreporting of notifiable diseases [28]. Underreporting has been associated with a number of factors, including clinicians' lack of time and motivation and the use of complicated and inconsistent paper forms.…”
Section: Phase 1: Literature Review Of the State Of The Artmentioning
confidence: 99%
“…To identify if there was significant underreporting of Viral meningitis, viral encephalitis, bacterial meningitis, malaria, etc Brabazon et al 2015 [28] hospitalized notifiable infectious diseases in Ireland Completeness A mobile-based disease surveillance system was developed, which improved the engagement of people in their own communities in the detection of infectious human and animal disease threats.…”
Section: To Design and Pilot Implementation Of A Syndromic Surveillanmentioning
confidence: 99%